Author Correction: High-latitude biomes and rock weathering mediate climate–carbon cycle feedbacks on eccentricity timescales - David De Vleeschouwer (Nature Portfolio, 2021)
A Correction to this paper has been published: https://doi.org/10.1038/s41467-021-21827-8